ANALYSIS OF THE FEASIBILITY OF CANDIED NUTMEG HOME INDUSTRY IN THE PULAU LEMUKUTAN VILLAGE OF SUNGAI RAYA KEPULAUAN SUB-DISTRICT - Ariyono Hutasoit; Adi Suyatno; Imelda . (Fakultas Pertanian Universitas Tanjungpura, 2020)
This research tries to analyze candied nutmeg home industry in Pulau Lemukutan Village, Sungai Raya Kepulauan District. Using descriptive analysis research methods and using 52 respondents. The results of this study indicate that the total costs incurred are Rp 3,804,472 per production, receipts obtained Rp 8,548,254, income earned Rp 5,172,138 and profit of Rp 4,743,782. Judging from the R / C value greater than 1, which is 2.24. Almost every Rp. 1.00 of the costs incurred, obtained Rp. 2.24. So, the candied nutmeg home industry is worth the effort. Labor productivity obtained Rp 5,121,014. This value is higher than the Bengkayang Regency UMK, which is Rp 2,364,776 per month. Capital productivity values obtained 1.46%. This value is greater than the savings interest which is 0.28%. More capital is needed if the candied nutmeg home industry is employed than combined.Keyword : Candied Nutmeg, Home Industry, Feasibility